Nurse's motivation and job satisfaction In providing nursing services during pandemic covid-19 - Dewi Murni; Yulastri Arif; Sidaria Sidaria; Nelwati Nelwati; Febrian Rahmat Suwandi; Silvia Zuela; Nicen Suherlin (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Nurse job satisfaction is an important component of a nurse's life because it will have an impact on patient safety, productivity, performance and service quality. Job satisfaction felt by nurses appears with the motivation. The development carried out can help novice nurses become experts. This is also a process of maintaining the quality and increasing the competence of nurses. Objective: To analyze the work motivation of nurses on job satisfaction in providing nursing services during the pandemic. Method: This descriptive correlational study was conducted using Cross Sectional approach involving 55 nurses. NonProbability Sampling and Purposive Sampling. This research instrument uses a questionnaire Application Needs A. Maslow - Nursalam. Data collection with frequency distribution analysis and SEM PLS 3.0 analysis. Results: The final analysis showed This study illustrates that prehospital nurses obtained a positive mean value of 0.414 end obtained a development value the mean has a positive value of 0.517. The results showed that there were 2 dimensions of nurse motivation that were significantly related to job satisfaction, namely the Recognition of Job Satisfaction (p 0.007) and the Development Dimension of Job Satisfaction (p 0.000), meaning (sig value) < 0.05. Achievement (p 0.638), Nature of Work (p 0.621) and Responsibility (p 0.951) sig value > 0.05. Conclusion: Focus on the development of education and knowledge, and make a planned schedule related to nurse development. the existence of full managerial support for nurses to be able to improve their performance so that nurses can achieve success in their careers. This can make nurses feel satisfied with the work they do Keywords: Motivation; Job Satisfaction; Nurse; Pandemic Covid-19